The Harriet Lane handbook : a manual for pediatric house officers - Harriet Lane Service (Johns Hopkins Hospital); Anderson, Camille C.; Kapoor, Sunaina; Mark, Tiffany E. (Philadelphia, PA : Elsevier, 2024)
"Every three years, The Harriet Lane Handbook is carefully updated by residents, edited by chief residents, and reviewed by expert faculty at The Johns Hopkins Hospital. Easy to use, concise, and complete, this essential manual keeps you current with new guidelines, practice parameters, pharmacology, and more. The 23rd Edition of this portable reference continues to be the most widely used and most recognized pediatric reference worldwide--an indispensable resource for pediatric residents, students, nurses, and all healthcare professionals who treat young patients."--
Part I: Pediatric acute care. Emergency and critical care management / Tai Kyung Hairston, MD and LeAnn McNamara, PharmD ; Tramatic injuries / Radhika Ghodasara, MD ; Toxicology / Sophie Crinion, MD ; Procedures / Maite E. Del Valle Rolon, MD -- Part II: Diagnostic and therapeutic information. Adolescent medicine / Yasamin Ege Sanii, MD andAmitte Rosenfeld, MD ; Analgesia and procedural sedation / Alexander James Jaksic, MD and Divya Madhusudhan, MD ; Cardiology / Alexander Tang, MD and James Ting, MD ; Dermatology / Allison Haley, MD and Katherine Cummings, MD ; Development, behavior, and development disability / Brenna M. Beck, MD MEd and Christle Nwora, MD ; Endocrinology / Rashmi Pashankar, MD ; Fluids and electrolytes / Joniqua Ceasar, MD ; Gastroenterology / Elshaddai Ephrem, MD ; Genetics : metabolism and conditions with disinctive appearance / Jacqueline Wood, MD, MA ; Hematology / Joan Park, MD ; Immunology and allergy / Samantha E. Leong, MD ; Immunoprophylaxis / Lindsay Sheets, MD ; Microbiology and infectious Disease / Amali Gunawardana, MD and Ashley Wallace, Wu, MD ; Neonatology / Elizabeth Lee, MD ; Nephrology / Ryan Handoko, MD ; Neurology / Hannah E. Edelman, MD, PhD and Maera J. Stratton, MD ; Nutrition and growth / Audrey Companiony Hopkins, MD ; Oncology / Lawrence Gersz, MD, MBA and Rebecca Xi, MD ; Palliative care / Sapna Desai, MD ; Psychiatry / Jelina Marie V. Castillo, MD, MPH ; Pulmonology and sleep medicine / Saskia Groenewald, MD ; Radiology / Urveel Mukesh Shah, MD ; Rheumatology / Emma Vaimberg, MD -- Part III: Reference. Blood chemistry and body fluids / Camille C. Anderson, MD ; Biostatistics and evidence-based medicine / Michael R. Rose -- Part IV: Formulary. Drug dosages / Carlton K.K. Lee, PharmD, MPH ; Drugs in kidney failure / Elizabeth A.S. Goswami, PharmD and Katherine Hapgood, PharmD
Includes ebook access
Bibliographical references available online
Includes index
Keywords: Pediatrics -- Handbooks, manuals, etc